Impactos do projeto de transposiç\~ao do Rio S\~ao Francisco na agricultura irrigada no nordeste setentrional - César Nunes de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– Currently, a large amount of the Federal Government's resources is being applied in the implementation of the S\~ao Francisco river water transfer project in the Northeast region of Brazil. This project aims to increase water supply for multiple uses in part of the Semi-Arid Northeastern region. Specifically the states of Ceará, Pernambuco, Paraíba and Rio Grande do Norte will be the beneficiaries of this project. Among the expected benefits include the development of some irrigated agriculture projects in this region. This study was composed of five parts, including the introduction and conclusion: the second part, addressed the issue of the current stage of development of irrigated agriculture in the Northeast region. From this overview on the current situation, it was possible to discuss the prospects for development of irrigated agriculture in this region resulting from the increased water supply. In the forth section, the focus fell on the existing constraints to the development of irrigated agriculture.
Keywords: Q15; Q25; 330